The rice F-box protein KISS ME DEADLY2 functions as a negative regulator of cytokinin signalling - Kim, Hyo Jung (Landes Bioscience, 2013)
Cytokinins are plant hormones that play critical roles in growth and development. We recently determined that the transcriptional response to cytokinin of Arabidopsis is modulated by the KISS ME DEADLY (KMD) family of F-box proteins. Here we demonstrate a conserved function for a member of the rice KMD family. Ectopic overexpression of OsKMD2 in Arabidopsis results in decreased cytokinin sensitivity based on a hypocotyl growth response assay, the decrease in sensitivity correlating with a decrease in the levels of the transcriptional regulator AtARR12. Furthermore, OsKMD2 directly interacts with AtARR12 based on yeast two-hybrid and co-immunoprecipitation assays. These results indicate that both monocots and dicots employ a similar KMD-dependent mechanism to regulate the transcriptional response to cytokinin.